2006
DOI: 10.1159/000092234
|View full text |Cite
|
Sign up to set email alerts
|

Acid Susceptibility of Arrested Enamel Lesions: In situ Study

Abstract: Arrested lesions are more resistant to a new cariogenic challenge, but the degree of surface rehardening needed to achieve this is unknown. The aim of this in situ study was to analyze the acid susceptibilityof newly formed and arrested enamel lesions with known arrestment period and surface microhardness. Six individuals wore an oral appliance with human enamel blocks for 3 periods: (1) 21 days of demineralization due to plaque accumulation and cariogenic challenge, 4 blocks/person (nonfluoride dentifrice); (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…One possible explanation is that the mineral gain observed during the lesion arrestment may be very slow, taking years to achieve the original hardness values. 26 Maltz et al 27 observed significantly lower micro hardness values in clinically arrested non-cavitated lesions compared to sound surfaces after 75 days of control. Other possibility is that the changes in lesions organic content may modify the fluorescence measurements rather than mineral content.…”
Section: Discussionmentioning
confidence: 96%
“…One possible explanation is that the mineral gain observed during the lesion arrestment may be very slow, taking years to achieve the original hardness values. 26 Maltz et al 27 observed significantly lower micro hardness values in clinically arrested non-cavitated lesions compared to sound surfaces after 75 days of control. Other possibility is that the changes in lesions organic content may modify the fluorescence measurements rather than mineral content.…”
Section: Discussionmentioning
confidence: 96%
“…This is possibly explained due to the mechanical properties that change with aging and the medical conditions of the subjects, as well as other conditions, such as exposure to fluoride and cariogenic challenges that occur in the oral cavity. 21 Additionally, the consistent, standardized preparation of specimens is laborious and time-consuming due to their small dimensions. Unfortunately, it is not possible to test the enamel surface without changing its morphology and microstructure, because microhardness testing requires a smooth, plane surface.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, in vitro and in situ studies applying different forms of topical fluoride demonstrated that, once inactivated, a lesion had higher acid resistance to new cariogenic challenges than sound enamel. This finding was to a large extent explained by the ability of fluoride to reduce demineralization and enhance remineralization [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%